Nutrient Contents of the Freshwater Crab, Isolapotamon bauense from Sarawak, Malaysia (Borneo) - Jongkar Grinang; Pang Sing Tyan; Andrew Alek Tuen; Indraneil Das (Tropical Life Sciences Research, 2017)
Data on nutrient contents of freshwater crabs are important for ecological studies and species conservation assessments, especially when the species concerned is threatened among others by habitat destruction and uncontrolled resources utilization. Indeed comprehensive biological information is required to reconcile the needs between sustainable resources utilization and conservation of the species. This study documents the nutrient contents of a freshwater crab, Isolapotamon bauense which is listed as ‘Vulnerable’ in the IUCN Red List of Threatened Species and also being harvested by local community for dietary supplement. Results show that muscles of the freshwater crab contain a substantial amount of nutrients in particular water content (male = 79.31 ± 2.30 %, female = 77.63 ± 0.56 %), protein (male = 77.47 ± 6.11 %, female = 63.28 ± 3.62 %), magnesium (male = 51.48 ± 16.10 mg/g, female = 39.73 ± 6.99 mg/g) and calcium (male = 25.50 ± 6.98 mg/g, female = 39.73 ± 6.99 mg/g). Means of nutrient contents between male and female crabs are not significantly different. It is estimated that an individual of I. bauense with weight range of 56–139 g contained on average of 0.35 ± 0.15 g of protein. Our estimation also shows that the number of individuals of the freshwater crab required to meet the recommended daily protein intakes of the community concerned is in the range 35–96 individuals for children, 130–188 individuals for adolescents, 171–179 individuals for men and 149–159 individuals for women. The results imply that harvesting of wild I. bauense as a source of protein supplement naturally may not be practical because of its relatively low population abundance, and conservation of the species for its ecological roles may thus be preferred. Data mengenai kandungan nutrien ketam air tawar adalah penting untuk kajian ekologi dan penilaian pemuliharaan spesies, terutamanya apabila spesies yang berkenaan terancam, antara lain oleh pemusnahan habitat dan penggunaan sumber yang tidak terkawal. Maklumat biologi yang komprehensif diperlukan untuk menyelaraskan keperluan antara pemanfaatan sumber pemuliharaan dan pemuliharaan spesies. Kajian ini menyenaraikan kandungan nutrien ketam air tawar, Isolapotamon bauense yang disenaraikan sebagai ‘Kerentanan’ dalam Senarai Merah Spesies Terancam IUCN dan juga ditangkap oleh masyarakat tempatan untuk makanan tambahan. Keputusan menunjukkan bahawa otot ketam air tawar mengandungi sejumlah besar nutrien dalam kandungan air tertentu (jantan = 79.31 ± 2.30%, betina = 77.63 ± 0.56%), protein (jantan = 77.47 ± 6.11%, betina = 63.28 ± 3.62%) , Magnesium (jantan = 51.48 ± 16.10 mg / g, betina = 39.73 ± 6.99 mg / g) dan kalsium (jantan = 25.50 ± 6.98 mg / g, betina = 39.73 ± 6.99 mg / g). Kandungan nutrien antara ketam jantan dan betina tidak begitu ketara. Adalah dianggarkan bahawa seekor ketam I. bauense dengan julat berat 56–139 g yang mengandungi purata 0.35 ± 0.15 g protein. Pengiraan juga menunjukkan bahawa bilangan ketam air tawar yang diperlukan untuk memenuhi pengambilan protein harian yang disyorkan bagi masyarakat berkenaan adalah dalam lingkungan 35-96 ekor untuk kanak-kanak, 130-188 ekor untuk remaja, 171-179 ekor untuk lelaki dewasa dan 149-159 ekor untuk wanita dewasa. Hasilnya menandakan bahawa penangkapan I. bauense liar sebagai sumber suplemen protein semulajadi mungkin tidak praktikal kerana kelimpahan penduduknya yang agak rendah, dan pemuliharaan spesies untuk peranan ekologinya boleh diutamakan.